"They Did It": The Effects of Emotionalized Blame Attribution in Populist Communication. (August 2017) - Hameleers, Michael; Bos, Linda; de Vreese, Claes H.
How can we explain the persuasiveness of populist messages, and who are most susceptible to their effects? These questions remain largely unanswered in extant research. This study argues that populist messages are characterized by assigning blame to elites in an emotionalized way. As previous research pointed at the guiding influence of blame attributions and emotions on political attitudes, these message characteristics may explain populism's persuasiveness. An experiment using a national sample ( N = 721) was conducted to provide insights into the effects of and mechanisms underlying populist blame attribution with regard to the European and national levels of governance. The results show that emotionalized blame attributions influence both blame perceptions and populist attitudes. Identity attachment moderates these effects: Emotionalized blame attributions have the strongest effects for citizens with weaker identity attachments. These insights allow us to understand how populist messages affect which citizens.